Emergence and Evolution of Siraiki Prosaic Stories - Mai, Nasim; Masood Khan, Badar; Nayyar, Qudsia (sourcecoder, 2022)
Folk lore plays a concrete role in the building of solid literature. Every language has its Folk lore that shows the true picture of that nation. Folk lore of Siraiki language is also based on the wisdom of Hakra culture. Hakra civilization is the neighboring of Harappa and mohanjo daro. Folk tales of subcontinent provide the pillars to the European Folk lore’s. From the east to west these tales traveled in the past. Soldiers from Alexander’s Army and the traders of the west brought these Folk tales From India to Europe. Siraiki tales reflects the true scenario of the society. It depicts the reflection of the people of Siraiki wasabi.